Selective Mapping of Deep Brain Stimulation Lead Currents Using Acoustoelectric Imaging - Preston, Chet (Ultrasound Med Biol, 2018)
We describe a new application of acoustoelectric imaging (AEI) for noninvasive mapping of the location, magnitude, and polarity of current generated by a clinical deep brain stimulation (DBS) device. Ultrasound at 1 MHz was focused near the DBS device as short current pulses were injected across different DBS leads. A recording electrode detected the high frequency AE interaction signal. Linear scans of the US beam produced time-varying images of the magnitude and polarity of the induced current, enabling precise localization of the DBS leads within 0.70 mm, a detection threshold of 1.75mA at 1MPa, and sensitivity of 0.52±0.07 μV/(mA*MPa). Monopole and dipole configurations in saline were repeated through a human skullcap. Despite 13.8 dB ultrasound attenuation through bone, AEI was still >10 dB above background with a sensitivity of 0.56±0.10 μV/(mA*MPa). This poof-of-concept study demonstrates selective mapping of lead currents through a DBS device may be possible using noninvasive AEI.